The Role of CLEC-2 and Its Ligands in Thromboinflammation - Meng, Danyang; Luo, Man; Liu, Beibei (Frontiers in Immunology, 2021)
C-type lectin-like receptor 2 (CLEC-2, also known as CLEC-1b) is expressed on platelets, Kupffer cells and other immune cells, and binds to various ligands including the mucin-like protein podoplanin (PDPN). The role of CLEC-2 in infection and immunity has become increasingly evident in recent years. CLEC-2 is involved in platelet activation, tumor cell metastasis, separation of blood/lymphatic vessels, and cerebrovascular patterning during embryonic development. In this review, we have discussed the role of CLEC-2 in thromboinflammation, and focused on the recent research.